2007
DOI: 10.1016/j.dental.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Electric device improves bonds of simplified etch-and-rinse adhesives

Abstract: d e n t a l m a t e r i a l s 2 3 ( 2 0 0 7 ) 513-518 a v a i l a b l e a t w w w . s c i e n c e d i r e c t . c o m j o u r n a l h o m e p a g e : w w w . i n t l . e l s e v i e r h e a l t h . c o m / j o u r n a l s / d e m a Objectives. This study investigated the effects of an electric field produced by a new device for the application of etch-and-rinse adhesives on demineralized dentin surfaces. Electric device improves bonds of simplified etch-and-rinse adhesives Methods. Three simplified etch-and-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 26 publications
2
46
0
4
Order By: Relevance
“…So, it is believed that changing the network into a VERT network can enhance infiltration. Using this idea, Pasquantonio et al (2007) applied an electric field to demineralized dentin and showed that it improved bonding. One of the possible reasons could be that the field is reorienting the network into a VERT network.…”
Section: On the Infiltration Front Through The Networkmentioning
confidence: 97%
“…So, it is believed that changing the network into a VERT network can enhance infiltration. Using this idea, Pasquantonio et al (2007) applied an electric field to demineralized dentin and showed that it improved bonding. One of the possible reasons could be that the field is reorienting the network into a VERT network.…”
Section: On the Infiltration Front Through The Networkmentioning
confidence: 97%
“…18 Incomplete infiltration by the adhesive resins through the demineralized zone may result in unprotected collagen and carbonated apatite crystallites that are vulnerable to enzymatic degradation and acid dissolution, respectively. 1,9,10,22,23 Nevertheless, despite the finding that the use of continuous electric current during adhesive application increased microtensile bond strength and reduced interfacial nanoleakage expression, [18][19][20][21] no conclusive hypotheses on the mechanisms sustaining the bonding increase were provided. It has been hypothesized that electricity may either affect surface wettability or directly influence adhesive monomer impregnation through iontophoretic forces that are superimposed to the polar monomers contained in the resin blends of the modern adhesive system.…”
Section: Introductionmentioning
confidence: 98%
“…16,17 Recent studies revealed that a new electric device (ElectroBond; SETI, Rome, Italy) could be useful to improve resin infiltration of etch-and-rinse and self-etch adhesives. [18][19][20][21] The rationale for applying a dentine adhesive under an electric current is to improve adhesive infiltration of the demineralized dentine. 18 Incomplete infiltration by the adhesive resins through the demineralized zone may result in unprotected collagen and carbonated apatite crystallites that are vulnerable to enzymatic degradation and acid dissolution, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term bonding is threatened by disaggregation of the hybrid layer owing mainly to the activation of dentin MMPs. Several methods have been suggested to achieve superior infiltration of monomers, to inhibit the breakdown of collagen fibrils, and to reduce aging water sorption, for example: using hydrophobic adhesives following the use of all-in-one adhesive primers, which have a low level of water sorption and solubility King et al, 2005), application of multiple layers , lengthening the curing time (Cadenaro et al, 2005;Cadenaro et al, 2006), increasing solvent evaporation (van Landuyt et al, 2005) and using electric current (Pasquantonio et al, 2007).…”
Section: Inhibiting Degradation Of Collagen In Dentin -Mmp Inhibitorsmentioning
confidence: 99%